Global prevalence of anorexia of aging: a systematic review and meta-analysis - Fernandez, Shirley Steffany Muñoz; Cipolli, Gabriela Cabett; Merchant, Reshma Aziz; Moreira, Virgílio Garcia; Klompenhouwer, Tatiana; Pain, Andreia; Ribeiro, Sandra Maria Lima; Duque, Gustavo; Bauer, Jürgen M.; Landi, Francesco; Cederholm, Tommy; Aprahamian, Ivan (Maturitas, 2025)
Anorexia of aging is a major geriatric syndrome that contributes to the development of malnutrition, frailty, and other adverse health outcomes, including death. However, its prevalence has not been clearly established. We examined the scientific literature to estimate the global prevalence and incidence of anorexia of aging, and its trends based on diagnostic tools, settings, and geographical location. A systematic search was conducted in PubMed, Scopus, Web of Science, and EMBASE from the date of database inception to July 2024. Observational cross-sectional and longitudinal studies in adults aged 60 years or more reporting the prevalence of anorexia of aging were included. The quality of the studies was assessed using the Newcastle-Ottawa Scale. Random-effects meta-analysis was used to estimate the pooled effects. A total of 40 studies were included in the systematic review. Among these, 36 studies with a total sample size of 29,864,296 individuals were included in the meta-analysis. The overall pooled prevalence of anorexia of aging was 22.7 %, and its incidence was 3.78 %. This prevalence estimate remained relatively steady from 2011 to 2024. The highest prevalence was found in the inpatient population, at 34.7 %, and the most used tool was the Simplified Nutritional Appetite Questionnaire. A significantly higher prevalence was observed in South America, at 27.1 %. Our findings highlight that, globally, more than one-fifth of older populations had anorexia of aging, and they illustrate the need for a global consensus on its diagnosis.
Online verfügbar: 21. Mai 2025, Artikelversion: 23. Mai 2025
Gesehen am 24.09.2025